Culturological potential of the creative person directed by problems of modern education (Journal of Philosophy Culture and Political Science, 2019)
The basic problems of development of culturological potential of the creative person in a context of modern formation are shown. The short complex of «technologies» on creation of the expanded social space for assistance in development of creative persons is offered.